PROFILING THE ROLE OF EMOTIONAL LABOUR AND ORGANIZATIONAL CULTURE ON EMPLOYEE ENGAGEMENT AMONG NURSES - Mazlina Che Malek; Nadwatul Husna Mustapha, (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2024)
This study aims to understand the influence of emotional work, organizational cultural support, and effective emotional management on the involvement and commitment of nurses in a public teaching hospital in Malaysia. Through interviews with five nurses, this study identified four main themes that affect their well-being and commitment: Emotional Stress and Fatigue, Organizational Support and Appreciation, Commitment and Motivation, and the Effects of Burnout and Despair. High emotional stress and the absence of a supportive organizational culture were reported to reduce motivation and increase the intention to quit among nurses. This study recommends that hospital management strengthen emotional support and improve organizational culture to reduce the risk of burnout and increase nurse engagement. These findings contribute to the existing literature in the field of emotional labor and human resource management in the healthcare sector, particularly in understanding the unique needs of nurses in Malaysia.